Innovations in Developing Power Quality in Young Boxers - Usmanov Zoxidjon; Mahmudova Sadoqatkhon (Genius Journals, 2022)
This article analyzes the results of a questionnaire survey aimed at improving the speed-strength qualities of young boxers (on the example of BOSM coaches).
Keywords: Loading; functional; physical training; exercise